INTELLIGENCE SYSTEM OF SCENARIO CONTROL OF BAKING PRODUCTION - Шаруда, Світлана Сергіївна; Кишенько, Василь Дмитрович (Eastern-European Journal of Enterprise Technologies, 2010)
Impotents of intellection systems for process control within bread making was shown. Multipurpose control algorithm and basic steps for intellection system were described.